Provision of Antiretroviral Therapy in South Africa: The Nuts and Bolts. Issue 3 (April 2014) - Bekker, Linda-Gail; Venter, Francois; Cohen, Karen; Goemare, Eric; Van Cutsem, Gilles; Boulle, Andrew; Wood, Robin
Public sector antiretroviral provision had a slow start in South Africa despite a raging epidemic and a World AIDS conference that shed significant public light on the disparities of therapy access globally. This was largely due to political prevarication in the midst of AIDS denialism. There has been an unprecedented expansion in the HIV treatment programme since 2008. As a result, South Africa now has the largest number of patients on antiretroviral drugs in the world, and South African life expectancy has increased by more than a decade. However, this has led to a number of fiscal, logistic and operational challenges that the country must face as the treatment programme continues to expand. Challenges include increasing detection within communities, linkage and retention in care, while strengthening operational support functions such as consistent drug supply, health staffing and infrastructure, diagnostic services, programme monitoring and sustainable financing. As a middle-income country, albeit with marked income inequality, and the heaviest HIV burden in the world, South Africa is a test case of whether a large-scale public health programme can boast of success in the face of numerous other health-system challenges.